The b’x Region of Yeast Protein Disulfide Isomerase is Not Essential for Saccharomyces cerevisiae Viability at 30 °C - . PURKAN; LALU RUDYAT TELLY SAVALAS; MULIAWATI SINDUMARTA; DESSY NATALIA (Microbiology Indonesia, 2009)
Protein disulfide isomerase (PDI) catalyzes thiol oxidation, reduction and isomerization of disulphide bond of cell surface and secreted proteins. Yeast PDI1 consists of two catalytic domains (a and a’) which are separated by two non-catalytic domains (b and b’), and a x region linked the b’ and a domains. The b’ domain is important for the non-covalent binding of partially folded protein. To understand the contribution of b’ domain and x-linker of yeast PDI1 we have deleted the b’x and investigated its functional role in vitro and in vivo. Yeast PDI1 without b’x region retained only 50% activity and became more sensitive toward Proteinase K. Interestingly, yeasts containing full length PDI1 and pdi1Db’x showed approximately the same growth rate. However, the yeast pdi1Db’x mutant growth impaired severely at 37 °C compared to that of the full length PDI1. Our results suggested that the a-b-a’-c domains of PDI seems to be sufficient to support the growth of yeast cells in normal condition, but the b’x region might be essential in assisting refolding of highly accumulated unfolded protein at high temperature (37 °C).